Highly Sensitive Amperometric α-Ketoglutarate Biosensor Based on Reduced Graphene Oxide-Gold Nanocomposites - Gang Peng; Yadong Yu; Xiaojun Chen; He Huang (International Journal of Analytical Chemistry)
Herein, a rapid and highly sensitive amperometric biosensor for the detection of α-ketoglutarate (α-KG) was constructed via an electrochemical approach, in which the glutamate dehydrogenase (GLUD) was modified on the surface of reduced graphene oxide-gold nanoparticle composite (rGO-Aunano composite). The rGO-Aunano composite was one-step electrodeposited onto glassy carbon electrode (GCE) surface and was characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and electrochemical techniques. In addition, the rGO-Aunano/GCE was also found to electrocatalyze the oxidation of β-nicotinamide adenine dinucleotide (NADH) at the peak potential of 0.3 V, which was negatively shifted compared with that at bare GCE or Aunano/GCE, illustrating better catalytic performance of rGO-Aunano. After the modification of GLUD, the GLUD/rGO-Aunano/GCE led to effective amperometric detection of α-KG through monitoring the NADH consumption and displayed a linear response in the range of 66.7 and 494.5 μM, with the detection limit of 9.2 μM. Moreover, the prepared GLUD/rGO-Aunano/GCE was further evaluated to be highly selective and used to test α-KG in human serum samples. The recovery and the RSD values were calculated in the range of 97.9–102.4% and 3.8–4.5%, respectively, showing a great prospect for its real application.